High school students’ perceived performance and relevance of chemistry learning competencies to sustainable development, action competence, and critical thinking disposition - Ramirez Hazel Joyce; Paderna Edwehna Elinore (Chemistry Teacher International)
Chemistry is deeply interconnected with various aspects of sustainability. However, enabling students to analyze these interconnections requires adequate support in learning. Moreover, few studies have explored the connection between students’ perceptions of chemistry learning competencies and their sustainability competencies that could be the basis for improving pedagogical practices. Therefore, this research investigated Filipino Grade 12 students’ perceived performance and relevance of chemistry learning competencies to sustainable development. Moreover, this study explored the students’ sustainability competencies, specifically action competence and critical thinking disposition. The Performance-Relevance Grid Analysis categorized the learning competencies based on the extent of perceived performance and relevance. Furthermore, the analysis also showed a correlation between students’ perceived performance and relevance (p = 0.015). Additionally, critical thinking disposition was found to be correlated with students’ perceived performance (p = 0.002) and relevance of chemistry learning competencies (p = 0.036) as well as with action competence (p < 0.001). Research findings provide crucial insights for future research and practice that could drive the integration of sustainability in chemistry education. This integration not only enhances the relevance of chemistry, but also encourages students to see the broader implications of their studies in the context of sustainable practices and societal impact.